Convergence of a high-order compact finite difference scheme for a nonlinear Black-Scholes equation - Michel Fournié; Bertram Düring; Ansgar Jüngel (University of Konstanz, Center of Finance and Econometrics (CoFE), 2004)
A high-order compact finite difference scheme for a fully nonlinear parabolic differential equation is analyzed. The equation arises in the modeling of option prices in financial markets with transaction costs. It is shown that the finite difference solution converges locally uniformly to the unique viscosity solution of the continuous equation. The proof is based on a careful study of the discretization matrices and on an abstract convergence result due to Barles and Souganides.
urn:nbn:de:bsz:352-opus-11696
Keywords: 330; High-order compact finite differences; numerical convergence; viscosity solution; financial derivatives; Black-Scholes-Modell; Nichtlineare Optimierung; Theorie